(3GdeZfj aj GdHjWQIs - (3YeQ Hf jhSa Hf YeQ Hf Ydj Hf QShd, CHh MaU, eegO GdOjf, Gdedc GdCTQa,J (B696 (3g` s
(3BNQgG (B:s
(3hjfTa GdehVY ef CKQ GdHQGe dG jRjO Ydjg bWY ChdkG , gcPG jaYd MJi JSJced CQHYhf jhekG , aEfgG JHQC Ef TGA Gddg JYGdi s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B6s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B237 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WH (B6) s
Keywords: (3GdWHs